EMPLOYEE PERFORMANCE DETERMINATION: LEADERSHIP STYLE, INDIVIDUAL CHARACTERISTICS, AND WORK CULTURE (A STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE) - Djoko Setyo Widodo (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that affect employee performance, namely: Leadership style, individual characteristics and work culture, a study of Human Resource Management literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Leadership Style has an effect on Employee Performance; 2) individual characteristics affect employee performance; and 3) work culture has an effect on employee performance.